Management of Magnetic Resonance Imaging Waiting Lists - Lightfoot, Christopher B.; Hsieh, Margaret (DALHOUSIE MEDICAL JOURNAL, 2005)
Management of MRI waiting lists in Canada is inadequate. There is very little medical literature addressing this important topic. Increased capital investment by government might not be adequate to reduce wait times. We sought the impact of a local private MRI clinic on the region‘s public health care wait times. Wait times surprisingly increased following the opening of this private MRI clinic and did not significantly decrease over the next six months. However, this analysis was complicated by the closure of one of the public MRI sites and the use of an MRI machine at a paediatric tertiary care centre for some adult patients. Increased resources directed specifically towards the implementation of standards and accountability as well as capital and infrastructure investment might improve current and future delivery of diagnostic imaging.